Nanoporous Microneedle Arrays Effectively Induce Antibody Responses against Diphtheria and Tetanus Toxoid - de Groot, Anne Marit (Front Immunol, 2017)
The skin is immunologically very potent because of the high number of antigen-presenting cells in the dermis and epidermis, and is therefore considered to be very suitable for vaccination. However, the skin’s physical barrier, the stratum corneum, prevents foreign substances, including vaccines, from entering the skin. Microneedles, which are needle-like structures with dimensions in the micrometer range, form a relatively new approach to circumvent the stratum corneum, allowing for minimally invasive and pain-free vaccination. In this study, we tested ceramic nanoporous microneedle arrays (npMNAs), representing a novel microneedle-based drug delivery technology, for their ability to deliver the subunit vaccines diphtheria toxoid (DT) and tetanus toxoid (TT) intradermally. First, the piercing ability of the ceramic (alumina) npMNAs, which contained over 100 microneedles per array, a length of 475 µm, and an average pore size of 80 nm, was evaluated in mouse skin. Then, the hydrodynamic diameters of DT and TT and the loading of DT, TT, and imiquimod into, and subsequent release from the npMNAs were assessed in vitro. It was shown that DT and TT were successfully loaded into the tips of the ceramic nanoporous microneedles, and by using near-infrared fluorescently labeled antigens, we found that DT and TT were released following piercing of the antigen-loaded npMNAs into ex vivo murine skin. Finally, the application of DT- and TT-loaded npMNAs onto mouse skin in vivo led to the induction of antigen-specific antibodies, with titers similar to those obtained upon subcutaneous immunization with a similar dose. In conclusion, we show for the first time, the potential of npMNAs for intradermal (ID) immunization with subunit vaccines, which opens possibilities for future ID vaccination designs.